A novel MKK gene (AjMKK3/6) in the sea cucumber Apostichopus japonicus: Identification, characterization and its response to pathogenic challenge. Issue 61 (February 2017) - Wang, Yi; Chen, Ge; Li, Kaiquan; Sun, Jingxian; Song, Jian; Zhan, Yaoyao; Zhang, Xiangxiang; Yang, Limeng; Chang, Yaqing
Abstract: The mitogen-activated protein kinase kinases (MKKs) are key components of MAP kinase (MAPK) cascades and function as redox-regulated signaling factors in pathological and physiological processes. In this study, we identified a novel MKK3/6 gene in the sea cucumber Apostichopus japonicus (designated as AjMKK3/6 ) by transcriptome database mining and rapid amplification of cDNA ends (RACE) approaches. Sequence analysis and protein structure prediction showed that AjMKK3/6 is highly conserved as compared to those from other invertebrate and vertebrate species. Molecular phylogeny result revealed that AjMKK3/6 exhibited a closest relationship with that from Strongylocentrotus purpuratus . Quantitative real-time PCR was employed to determine the expression profiles of AjMKK3/6 in healthy adult A. japonicus tissues and in coelomocytes after Vibrio splendidus infection in vivo, respectively. As results shown, AjMKK3/6 was ubiquitously expressed in all examined tissues of healthy adult A. japonicus with a relative expression level from high to low as body wall > tube feet > coelomocytes > respiratory tree > intestine > longitudinal muscle. Significant expression changes of AjMKK3/6 in coelomocytes were observed at 12 h- and 72 h-after V. splendidus infection, respectively. In general, the current study will enrich our knowledge of characterizations and immno-functions of MKK3/6 in sea cucumbers. Highlights: AjMKK3/6 in the sea cucumber Apostichopus japonicus was cloned and characterized. AjMKK3/6 expressed ubiquitously in all examined tissues of adult A. japonicus. The expression profiles of AjMKK3/6 in coelomocytes altered after pathogen challenge in vivo .